Skill India Mission: Achievements and Challenges: Exploring the Impacts of Skill India Mission on Youth Employment and Economic Growth (Journal of Advances and Scholarly Researches in Allied Education, 2019)
‘Skill India Mission’ has been launched by NaMo Government of India in march 2015.According to NaMo, skill India won’t be just a program but a movement. Here, Youth who are jobless, college and school dropouts, along with the educated ones, from rural and urban areas, all will be given value addition. The idea is to raise confidence, improve productivity and given direction through proper skill development. So that none of the youths remains unemployed and country unemployment problem also gets reduced, it is time to open up avenues by which the youth accepts responsibility and no one remains idle because an idle youth is a burden to the country. The economy should concentrate on job creation and social security schemes with the new approach towards ‘Skill India’, The country can definitely move forward towards its targeted results.